Effect of Surface Layers in Sliding Contact of Viscoelastic Solids (3-D Model of Material) - Torskaya, Elena V.; Stepanov, Fedor I. (Frontiers in Mechanical Engineering, 2019)
Sliding contact of a smooth indenter and a two-layered half-space is considered to take rheological properties of materials into account. A viscoelastic layer bonded with a rigid half-space is analyzed as well as the opposite viscoelastic half-space covered by a rigid layer. The problem is formulated as quasi-static. A numerical-analytical method of solution is based on a boundary element method and an iteration procedure. A new analytical solution is used to calculate the influence of coefficients for the computation procedure. Contact pressure, energy dissipation and internal stresses are analyzed depending on sliding velocity, layer thickness and Poisson's ratio.